Interview with Federico Mayor Zaragoza, Minister of Education (1981-1982) and General Director of the UNESCO (1987-1999) - González-Moreno, Javier (Historia y Memoria de la Educación, 2024)
Since its founding in 1945 after the victory over fascism in World War II, the United Nations Educational, Scientific and Cultural Organization (known by its acronym in English: UNESCO) has been one of the most influential entities on international educational and cultural policies. In this interview we spoke with Federico Mayor Zaragoza, who held inportant positions in this organization between 1978 and 1999, including that of General Director, about its evolution and its influence on the policies of various countries, especially in relation to its main mission: erect «the bastions of peace» in the minds of human beings. Likewise, we talked about Federico Mayor Zaragoza’s previous experience in various positions in the educational administration in the 70s, especially about the relevance of various personalities in those years and the dynamics of the Transition that he experienced so closely